Insurance in developing countries: privatization of insurance enterprises and liberalization of insurance markets (United Nations New YorkUS, 1993)
Examines the motives for privatization and some of the problems associated with it. Looks at state insurance monopolies, public enterprise reinsurers and commercialization. Focuses on the Uruguay Round and deals with competitiveness of Third World insurance. Reviews cross-border trade and establishment trade and looks at opening developing countries insurance markets to foreign suppliers. Progress in Uruguay Round negotiations are also noted as well as options for developing countries.
DC